Early blood stream infection following allogeneic hematopoietic stem cell transplantation is a risk factor for acute grade III–IV GVHD in children and adolescents. Issue 2 (17th September 2017) - Sano, Hirozumi; Hilinski, Joseph A.; Qayed, Muna; Applegate, Kristy; Newton, Joanna G.; Watkins, Benjamin; Chiang, Kuang‐Yueh; Horan, John
Abstract: Background: Graft‐versus‐host disease (GVHD) remains a major cause of mortality and morbidity in allogeneic hematopoietic stem cell transplantation (HSCT). In adults, early blood stream infection (BSI) and acute GVHD (AGVHD) have been reported to be related. The impact of BSI on risk for AGVHD, however, has not been assessed in pediatric patients. Procedure: We conducted a retrospective analysis to test the hypothesis that early BSI (before day +30) predisposes allogeneic pediatric transplant patients to severe AGVHD. We analyzed 293 allogeneic HSCT performed at Children's Healthcare of Atlanta between 2005 and 2014 that met eligibility criteria. Results: The cumulative incidence of acute grade III–IV GVHD at 100 days after HSCT was 17.1%. In multivariate analysis, risk for acute grade III–IV GVHD was associated with HLA‐mismatched donor (hazard ratio [HR] = 4.870, P  < 0.001), and BSI between day 0 and +30 prior to AGVHD (HR = 3.010, P  = 0.001). Conclusions: These results indicate that early BSI appears to be a risk factor for acute grade III–IV GVHD. Further research is needed to determine if the link is causal.